EXPERIMENTS ON ARTIFICIAL PROPAGATION OF HILSA, TENUALOSA ILISHA (HAMILTON) - Sen, P R; De, D K; Nath, D (Indian Journal of Fisheries, 2011)
The note presents the results of successful rearing of hilsa larvae under captivity for four months. Artificial propagation of hilsa was tried by many workers (Wilson, 1909; Raj, 1917;Southwell and Prashad, 1918; Kulkarni, 1950) but none succeeded in rearing the resultant hatchlings beyond three days. Malhotra et ah (1969,1970 and 1979) successfully bred the fish by stripping the fresh-water stocks of hilsa available from Ganga at Sirsa, 50 km downstream of Allahabad. They were also successful in rearing the hatchlings for a longer period. Panicker et al. (1982) achieved limited success in the direction of propagating hilsa in Vallab Sagar (Ukai) reservoir at Gujarat. Bhanot and De (1984) reared hilsa fry obtained from fresh-water stretch of Hooghly river in freshwater pond for more than 2 years and the growth attained by the fish was found to be highly satisfactory.